The need of a weight management control program in judo: a proposal based on the successful case of wrestling - Sterkowicz Stanislaw; Nicastro Humberto; Franchini Emerson; Artioli Guilherme G; Solis Marina Y; Lancha Antonio H (Taylor & Francis Group, 2010)
Abstract Judo competitions are divided into weight classes. However, most athletes reduce their body weight in a few days before competition in order to obtain a competitive advantage over lighter opponents. To achieve fast weight reduction, athletes use a number of aggressive nutritional strategies so many of them place themselves at a high health-injury risk. In collegiate wrestling, a similar problem has been observed and three wrestlers died in 1997 due to rapid weight loss regimes. After these deaths, the National Collegiate Athletic Association had implemented a successful weight management program which was proven to improve weight management behavior. No similar program has ever been discussed by judo federations even though judo competitors present a comparable inappropriate pattern of weight control. In view of this, the basis for a weight control program is provided in this manuscript, as follows: competition should begin within 1 hour after weigh-in, at the latest; each athlete is allowed to be weighed-in only once; rapid weight loss as well as artificial rehydration (i.e., saline infusion) methods are prohibited during the entire competition day; athletes should pass the hydration test to get their weigh-in validated; an individual minimum competitive weight (male athletes competing at no less than 7% and females at no less than 12% of body fat) should be determined at the beginning of each season; athletes are not allowed to compete in any weight class that requires weight reductions greater than 1.5% of body weight per week. In parallel, educational programs should aim at increasing the athletes', coaches' and parents' awareness about the risks of aggressive nutritional strategies as well as healthier ways to properly manage body weight.